Robert Chambers - ”Participatory approaches to data gathering and anal ysis' (FULL WORKSHOP 2h) (IMA International, 2015)
A participatory workshop on ”Participatory approaches to data gatherin g and analysis' by Professor Robert Chambers, Research Associate, Inst itute of Development Studies, UK. https://www.ids.ac.uk/person/robert- c...